Om behovet av samsyn och riktlinjer - Magdalena Hulth (Utbildning & Demokrati)
On the Need for Consensus and Guidelines: Focus Group Discussions on Sexuality and Sexuality Education in Preschool. The article is based on a discourse analysis of focus group discussions with preschool practitioners in Sweden. It explores the professional considerations made in relation to children, sexuality, and Sexuality Education. Three subject positions emerge: the consensus-seeking teacher, characterized by uncertainty and a need for guidelines; the curriculum-oriented teacher, who uses the curriculum to support children’s rights; and the (reluctant) reporting teacher, who struggles between mandatory reporting and personal judgment. The study highlights the curriculum as a tool for professional competence, but that societal norms about children’s sexuality profoundly shape preschool practitioners’ professional considerations. This emphasizes the need for education and dialogue about children’s sexuality in preschool teacher education.